Karakteristik Manuskrip Al-Qur’an Pangeran Diponegoro: Telaah Atas Khazanah Islam Era Perang Jawa - Hasna, Hanifatul (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2019)
Prince Diponegoro who is the son of Sultan Hamengkubuwana III grew up in the community of kyai and santri. The education of his great-grandmother influenced the view of Prince Diponegoro who then liked Islamic works. The aristocratic legacy of Prince Diponegoro made himself courageous to lead the Java War against the Dutch. The peak of Java War in the Magelang left historical objects. Among them are Quranic manuscripts attributed to Prince Diponegoro. Unfortunately, many works do not discuss about the legacy of Prince Diponegoro. This paper examines a Quranic manuscript attributed as a legacy of Prince Diponegoro through a philological and codicological approach with the aim of knowing how the history and characteristic of the manuscript are. Through this paper, it can be known the characteristics of philology in Islamic studies through of the Quranic manuscripts. There are several prominent characteristics of the Mushaf, such as illuminations at manuscripts that seem luxurious and thick with Javanese culture. The use of rasm, punctuation, sign tajwid, and sign waqaf also characterizes the writing of manuscripts in the 19 th century in the Java War that is different from the mushaf that is developing now.